Movement and combustion characteristics of densified rice hull pellets in a fluidized bed combustor at elevated pressures. (15th June 2021) - Yang, Zhihao; Duan, Lunbo; Li, Lin; John Anthony, Edward
Graphical abstract: Highlights: The location of particles during pressurized combustion was studied. The combustion characteristics of particles were analyzed in different pressures. Quantitatively analyze the reason of better oxygen transport at elevated pressure. Abstract: Pressurized oxy-fuel fluidized bed combustion is regarded as a promising carbon capture technology, which can realize negative CO2 emission through burning biomass. However, given its high volatile content and low density, biomass has been frequently reported to demonstrate poor mixing in industrial FB combustors. Especially in the case of pressurized oxy-fuel combustion, the gas-solid flow in the reactor, fuel particle motion and combustion process will all change and influence each other, which is very important for the particle conversion process and the safety of boiler operation. To correlate the location information with the combustion process in pressurized oxy-fuel combustion, densified rice hull pellets, serving as a typical biomass, were selected as the fuel, and entire whole combustion process was recorded by a color video camera to facilitate the temperature measurement of the volatile flame and char particle by two-color pyrometry. The distribution of a densified rice hull pellet at any given location was obtained from statistics derived from the images. Results showed that the pressure and atmosphere change does not strongly affect the probability of densified rice hull pellets appearing at a given location during the devolatilization process itself. However, during the char combustion process, the probability of finding a particle at the bed surface increased with pressure whereas particle concentrations in the splash zone showed little change, despite the enhanced bubble collapse at elevated pressures. However, the temperature of the volatile flame and char particles increases with the pressure whereas the burnout time of biomass particle decreases due to better oxygen transport.